Genetics and Morphological Variations within Genus Callosciurus from Borneo - Muhammad Hanif Fikri, Mohamad Khirudin (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Callosciurus, which is a genus of squirrels that fall under the Family Sciuridae, is an example of Southeast Asia's mammalian group with great species diversity. However, precise genetic study on the Sciuridae is finite, apart from a few recent studies with limited sample site from Borneo. The main purpose of this study is to analyze the genetics and morphological variation within genus Callosciurus from Borneo. In this study, secondary data of Callosciurus from the museum of Faculty of Resource Science and Technology UNIMAS were being used. A total of 27 sequences were utilized to build a phylogenetic tree using neighbor-joining, maximum parsimony, and maximum likelihood methods. Sequence from GenBank were also used in this study to get the DNA sequence information of Callosciurus that are not available at the museum. Cytochrome c oxidase I (COI) were used as genetic marker with VF1 forward and VR1 reverse as primer. For morphological analysis, Principal Component Analysis (PCA) was conducted by using PAST software, using 24 individuals of Callosciurus with five morphometric characteristics based on external morphology. Results from this study declared that with high bootstrap value from phylogenetic analysis, the connection of the genus Callosciurus showed the existence of genetic divergence within this genus, and the genetic study result indicated that one sample from the museum had been misidentified as Callosciurus notatus. From the morphological analysis, the findings revealed that their morphometrics differ, and the species may be recognized by comparing tail to ventral length and head to body length. This proved that there is significant difference in genetic and morphological variation within the genus Callosciurus from Borneo.